Divergent paths : economic mobility in the new American labor market - Bernhardt, Annette D., 1964- (Russell Sage Foundation, 2001)
"The promise of upward mobility - the notion that everyone has the chance to get ahead - is one of this country's most cherished ideals, a hallmark of the American Dream. In today's volatile labor market, the tradition of upward mobility may be a thing of the past. In a competitive world of deregulating markets and demanding shareholders, many firms that once offered the opportunity for advancement to workers have remade themselves as leaner enterprises with more flexible work forces. DIVERGENT PATHS examines the prospects for upward mobility for workers in this changing economic landscape